2007
DOI: 10.1111/j.1365-294x.2007.03588.x
|View full text |Cite
|
Sign up to set email alerts
|

Population structure of an endemic vulnerable species, the Jamaican boa (Epicrates subflavus)

Abstract: The Jamaican boa (Epicrates subflavus; also called Yellow boa) is an endemic species whose natural populations greatly and constantly declined since the late 19th century, mainly because of predation by introduced species, human persecution, and habitat destruction. In-situ conservation of the Jamaican boa is seriously hindered by the lack of information on demographic and ecological parameters as well as by a poor understanding of the population structure and species distribution in the wild. Here, using nine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 51 publications
1
25
0
Order By: Relevance
“…However, five loci showed values lower than 0.7 indicating recent size reduction, while only one loci (GCPM_354) was even lower, lower than 0.43, which indicates significant population decline in the past (Garza & Williamson, 2001;Tzika et al, 2008). The mean value of G-W index was confirmed with alleles shifted mode distribution, confirming existence of recent size reduction within studied population.…”
Section: Viability Assessmentsupporting
confidence: 59%
“…However, five loci showed values lower than 0.7 indicating recent size reduction, while only one loci (GCPM_354) was even lower, lower than 0.43, which indicates significant population decline in the past (Garza & Williamson, 2001;Tzika et al, 2008). The mean value of G-W index was confirmed with alleles shifted mode distribution, confirming existence of recent size reduction within studied population.…”
Section: Viability Assessmentsupporting
confidence: 59%
“…DNA was unavailable for the 2004 male and his offspring. Samples were screened and genotyped at five microsatellite loci (table 1) newly developed for B. c. imperator following the method outlined by Booth et al [17], and at three additional loci developed by Tzika et al [18]. …”
Section: Methodsmentioning
confidence: 99%
“…Most of wildlife including mammals, birds, amphibians, reptiles, and so on is considered to be endangered or threatened because of illegal hunting, oriental medicine, habitat destruction. Especially, natural population of snakes in reptiles constantly declined, mainly because of predation by introduced species, human persecution, and habitat destruction (Tzika et al, 2008). A comprehensive assessment of population structure is one critical component for their effective conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Within the species, genetic differentiation on the basis of F ST value could be identified. Tzika et al (2008) reported that the F ST value of three populations for jamaican boa (Epicrates subflavus) was 0.093 (P⁄0.001). Among 5 populations of timber rattlesnake (Crotalus horridus), F ST values were ranged from 0.000 to 0.005 (Clark et (Park, 2010).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation